Mój Cekcyn. Fragmenty autobiograficzne - Wejland, Andrzej Paweł (Zeszyty Wiejskie, 2014)
The article contains, besides the introduction, three micro-narratives based on my personal memory of the village Cekcyn in the Tuchola Forest (Bory Tucholskie) – the memory of the place, but also of the people, their dialect and some other features of their regional culture. Each of the micro-narratives has a form of an autobiographical fragment (in the sense similar to that of a deliberately undeveloped literary fragment) in which my memory is complemented by the ethnographic details taken from sources and research reports as well as by more general anthropological concepts.